2022
DOI: 10.12697/poa.2021.30.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Peer relations linking overweight and obesity, and mediator factors among Turkish adolescents

Abstract: Depending on the individual’s body height and frame structure and body weight, obesity is considered both as a socially accepted norm in a society and as exceeding the accepted upper limits. The present study aimed to determine the associations between overweight and obesity, peer relationships, and nutritional and physical activity behaviour among Turkish adolescents. A cross-sectional study was conducted in Ankara, and the sample consisted of 402 adolescents (171 boys and 231 girls) aged between 12 and 17 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Peers also influence adolescents' BMI; the influence of peers on adolescents' BMI is that there is a prevailing social norm among adolescents regarding body size, where adolescents with overnutrition report lower self-esteem and body satisfaction and receive teasing about their weight from peer 52 . Therefore, interactions between adolescents and peers can affect their body perception through conversations related to appearance, modelling of peer diet behaviour, and perceptions of attitudes related to peer appearance 53 Research found that an increase in peers' BMI increases adolescents' BMI and the likelihood of overweight and obesity 54 .…”
Section: Relationship Between Variablesmentioning
confidence: 99%
“…Peers also influence adolescents' BMI; the influence of peers on adolescents' BMI is that there is a prevailing social norm among adolescents regarding body size, where adolescents with overnutrition report lower self-esteem and body satisfaction and receive teasing about their weight from peer 52 . Therefore, interactions between adolescents and peers can affect their body perception through conversations related to appearance, modelling of peer diet behaviour, and perceptions of attitudes related to peer appearance 53 Research found that an increase in peers' BMI increases adolescents' BMI and the likelihood of overweight and obesity 54 .…”
Section: Relationship Between Variablesmentioning
confidence: 99%